Investigations of a Gas Turbine Low-Emission Combustor Operating on the Synthesis Gas - Serhiy Serbin; Nataliia Goncharova (International Journal of Chemical Engineering)
Investigations of the working processes in a gas turbine low-emission combustor operating on the synthesis gas, in which the principle of RQL (Rich-Burn, Quick-Mix, and Lean-Burn) combustion technology is realized, have been performed. Selected concept of a gas turbine combustor can provide higher performance and lower emission of nitrogen oxides and demonstrates satisfactory major key parameters. Obtained results and recommendations can be used for the gas turbine combustor operation modes modeling, geometry optimization, and prospective power generation units design and engineering.